Assessment of transparency in provincial historic archives - Pacios Lozano, Ana R.; Martínez Cardama, Sara; Moro Cabero, Manuela (Information Science Journal, 2021)
The article discusses the findings on website transparency for 52 Spanish provincial historic archives and the Archivo Real y General de Navarra [royal and general archive of the province of Navarra], delivered by TransPa_BA software. This tool is based on and uses the parameters defined in the Metodología de Evaluación y Seguimiento de la Transparencia [transparency assessment and monitoring method, Spanish initials, MESTA]. A total of 22 indicators are proposed to measure active public disclosure by archives in keeping with the provisions of the national Transparency Act. The indicators and their respective parameters (form, reusability, dating and currency) constitute guidelines to enable archives to enhance transparency and accountability, reporting their activities and performance in key areas to society in general and their stakeholders in particular. Although the findings reveal some good practices, scant transparency-related information is provided. The improvements suggested refer not only to public disclosure, but also to how information is arranged, for neither visibility nor accessibility is optimal. This study will hopefully encourage collective learning, contributing to the gradual inclusion of more transparent information and the exclusion of any redundant elements present on these institutions’ websites.